The Interplay of Students’ School Engagement, School Self-Concept and Motivational Relations during Adolescence - Bakadorova, Olga; Raufelder, Diana (Frontiers in Psychology, 2017)
Existing literature evidences the association between adolescents’ school self-concept and engagement, both concepts being related to students’ perception of teachers and peers as motivators. However, few longitudinal studies explore the interplay of these factors. The present study aims to close this gap, applying latent cross-lagged panel design to two-wave data from German adolescent students (1088 8th grade students at T1 (Mage = 13.7, SD = .53; 53.9% girls) and 845 9th grade students at T2 (Mage = 14.86; SD = .57; 55% girls) from the initial sample). Besides direct effects, three cross-lagged over-time paths were found to be significant: Students’ perception of peers as positive motivators at the beginning of 8th grade (T1) positively predicts their behavioral school engagement at the end of 9th grade (T2), as well as emotional school engagement at the beginning of 8th grade positively predicts students’ perception of peers as positive motivators 1.5 years later. Furthermore, behavioral school engagement at T1 functions as a predictor of a student’s school self-concept at T2.